Life-cycle financial planning in Malaysia: Investment planning and strategies for the post-retirement period / Tan Hoe Kock - Tan, Hoe Kock (2012)
This study examines the extent Malaysians make financial preparations and their readiness for retirement and the predictors of retirement plans based on the life-cycle model that people seek to maintain their living standards by smoothing their consumption, as they age and face life’s various contingencies. The study delved into the concept of life-cycle financial planning, life-cycle theories of savings, consumption, and investing, and the critical issues surrounding the study of retirement, particularly investment planning strategies for financing consumption during the postretirement period. The three potential sources of post-retirement income for Malaysians are: a defined benefit (DB) pension for retired civil servants, the Employees Provident Fund (EPF) for employees in the private sector, and personal savings. A total of 990 questionnaires were distributed to respondents with a 55.2% return rate. A total of 12 main hypotheses were analysed using ordinary and hierarchical regression analyses, as circumstances justified. The results revealed that 24 of the hypotheses or sub-hypotheses were accepted and 34 rejected. Principally, the hypotheses have focused on four major areas, namely: (1) the relationship between age cohorts and orientation towards financial planning, (2) the current financial resources and expected retirement age, (3) the effect of interrelationships between confidence in the economy and financial planning preparation within the context of current financial resources, and (4) confidence in the economy and various levels of consumption. It was observed that, with the demographic variables being included in the overall models, nearly half the hypotheses have shown some positive v effect. These effects are mainly involved with orientation towards retirement planning, expected retirement age, confidence in the economy, current financial resources and financial planning preparation. There is also evidence to indicate that the interrelationships between age cohort and orientation towards financial planning generally have some degree of mediating effect from Malaysians’ confidence in the economy which may affect their plan for securing their post-retirement financial security. The implication was that not only should their individual perceptions of retirement planning become an increasingly important part of people’s long-term commitment throughout their life-cycle, financial planning must also assume the role as a self-directed life-long learning process, in view of the ever-changing and complicated financial environment. Another implication is that the anticipated pattern of real income in the future is a very crucial part of optimal consumption patterns.